Exosomal miR-2137 from cadmium-treated hepatocytes drives renal ferroptosis via GPX4 suppression and is alleviated by selenium - Wen, Qian; Qi, Meiyan; Wu, Yanjun; Ji, Weiwei; Zhan, Lixing (Frontiers in Cell and Developmental Biology, 2025)
Cadmium (Cd) is a toxic heavy metal that primarily affects the liver and kidneys. Despite greater Cd accumulation in the liver, Cd-induced oxidative damage is more pronounced in the kidney, suggesting the involvement of hepatorenal communication. However, the underlying mechanism remains unclear. To investigate Cd-induced hepatorenal toxicity, we established a Cd-exposed mouse model and assessed ferroptosis-related liver and kidney injury. Exosomes derived from Cd-exposed hepatocytes were isolated, and miRNAs targeting GPX4 were screened and identified. The role of GPX4-targeting miRNAs in mediating renal toxicity induced by hepatocyte-derived exosomes was evaluated in vivo using antagomirs. The protective effect of selenium (Se) supplementation against Cd-induced hepatic and renal damage was also examined. Cd exposure induced significant liver and kidney injury through GPX4-downregulated ferroptosis. Mechanistically, exosomes from Cd-treated hepatocytes were enriched in miR-2137, which targets renal GPX4 and promotes ferroptosis in the kidney. Injection of hepatocyte-derived exosomes alone reduced renal GPX4 levels in vivo, an effect that was reversed by miR-2137 antagomir treatment. Furthermore, Se supplementation restored GPX4 expression and protected both liver and kidney tissues from Cd-induced damage. These findings reveal a novel exosome-mediated hepatorenal communication pathway under Cd exposure, wherein hepatocyte-derived exosomal miRNAs contribute to distant renal injury. Targeting specific exosomal miRNAs or enhancing GPX4 expression via selenium may offer therapeutic strategies against Cd toxicity.